2021
DOI: 10.3390/en14217138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Consumers’ Adoption of Renewable Energy

Abstract: The purpose of this study was to evaluate the consumers’ adoption of renewable energy in Poland. The study focused on finding out the factors that influence the adoption of the technology, considering its importance in conserving the environment. The study was conducted using a quantitative method, with primary data collected from 467 households using renewable energy technology in Poland. The research adopted the TAM model. The independent variables of the study included renewable energy initial cost, environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…There were several other studies carried out exploring the adoption-determinants of solar (PV) systems around the world by different researchers. For instance, the adoptiondeterminants of renewable energy were evaluated using the TAM [8]. Among six factors of adoption, two, that is, (one) initial cost and (two) risk and trust, were not found to be significant.…”
Section: Literature Review On Solar (Pv) System's Adoptionmentioning
confidence: 99%
See 3 more Smart Citations
“…There were several other studies carried out exploring the adoption-determinants of solar (PV) systems around the world by different researchers. For instance, the adoptiondeterminants of renewable energy were evaluated using the TAM [8]. Among six factors of adoption, two, that is, (one) initial cost and (two) risk and trust, were not found to be significant.…”
Section: Literature Review On Solar (Pv) System's Adoptionmentioning
confidence: 99%
“…Among six factors of adoption, two, that is, (one) initial cost and (two) risk and trust, were not found to be significant. Ease-of-use, financial incentives, relative advantage, and environmental concerns were realized to be significant [8]. In determining the factors of residential PV systems, Schulte and Scheller [42] performed a meta-analysis and revealed that subjective norms, environmental concern, and novelty seeking related to and affected the perceived benefits and onward adoption intention.…”
Section: Literature Review On Solar (Pv) System's Adoptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The location decision of logistics centers and their performances are crucial, as they help companies not only minimize costs, traffic congestion, and environmental pollution levels, but also improve the scheduling system and vehicle routing [4][5][6][7]. This is especially the case with environmental concerns since it is not only the responsibility of logistics companies but also an issue for government and other stakeholders, as well as one of customers awareness [8].…”
Section: Introductionmentioning
confidence: 99%